The impact of COVID-19 pandemic on the preventive services in Qatar - Mohamed Ghaith Al-Kuwari; Mariam Ali Abdulmalik; Hamad Rashid Al-Mudahka; Ahmad Haj Bakri; Wadha Ahmed Al-Baker; Shaikha Sami Abushaikha; Mujeeb Chettiyam Kandy; John Gibb (SAGE Publishing, 2021)
Background: In March 2020, Qatar started reporting increased numbers of COVID-19 cases. At that stage, containment measures were put in place. The health authority in Qatar developed an emergency action plan to respond to the outbreak with the Primary Health Care as the main component of that response and suspended all non-urgent services including preventive health services. The aim of the retrospective analysis to measure the Impact of COVID-19 on the preventive services provided in Qatar. Methods: A retrospective data analysis was conducted for all the preventive services utilization volume across the 27 PHCC health centres from the 1st of January 2017 to the 31st of July 2020. Results: With 17,012 no-show appointments, well-baby and Immunization services utilization demonstrated a reduction of 40% in May and started to come back to volumes higher than expected in June. The breast cancer and colorectal cancer screening programmes expected volumes demand has dropped by 100% in comparison to 2017 demand due to their respective appointments' cancelation. Wellness services only met 20% of its projected utilization in April, however, the services picked up in June. Conclusion: These findings will guide the public health policymakers to understand the effects COVID-19 on preventive services and the risk of having an increased number of outbreaks for childhood communicable disease, cancer cases with delayed diagnosis due to the screening services suspension. In addition, the plan will address the increased number of sedately behaviour due to the service's reduced utilization of wellness services.